Investigations into explosion characteristics of ANFO and granular aluminium mixtures - Evergen, T. (Informa UK Limited, 1993)
ABSTRACT In this paper the changes in thermodinamic characteristics of the gases released from the explosion of ANFO and Al powder mixtures in different quantities are investigated theoretically and oftimum values are determined. In:the first part, density, grain size and chemical content of ALMEG XX granular aluminium powder are given. In the 2nd, 3rd and 4th parts, reaction temperatures and specific energy values obtained after the explosion of ANFO and Al powder mixtures are given theoretically according thermodinamic laws.